Kedudukan dan Karakteristik Peraturan Menteri dalam Melaksanakan Urusan Pemerintahan Menurut Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Illahi, Beni Kurnia (Jurnal Legislasi Indonesia, 2022)
Increasing regulation is unavoidable in Indonesia. This study will discuss one of the problems in the formation of legislation, which are the characteristics of the formation of ministerial regulations in carrying out government affairs. As referred to in Article 8 paragraph (2) of Law Number 12 of 2011 concerning the Establishment of Legislation, it states that the Ministerial Regulation is formed based on 2 things, the first is ordered by a higher statutory regulation, the second is formed based on the authority. This is intended to answer the following questions, does the minister have the authority to formulate legislation based on the 1945 Constitution. Then how to determine and design the characteristics of the formation of ministerial regulations that are formed based on orders from higher laws and regulations and ministerial regulations that are formed based on the decree of authority according to the 1945 Constitution. This research uses normative legal research methods with descriptive research specifications and is analyzed through literature study and data analysis methods using juridical-qualitative. The results of the research will later find the characteristics of the formation of ministerial regulations which are formed based on orders from higher legislation and which are formed based on orders of authority according to the 1945 Constitution. This is expected as a proposal/idea to lawmakers to try to rearrange the limits of authority in the formation of legislation based on the 1945 Constitution.